Unsolved Issues in Thymic Epithelial Tumour Stage Classification: The Role of Tumour Dimension - Carolina Sassorossi; Pietro Bertoglio; Filippo Lococo; Gloria Santoro; Elisa Meacci; Dania Nachira; Maria Teresa Congedo; Jury Brandolini; Matteo Petroncini; Adriana Nocera; Diepriye Charles-Davies; Piergiorgio Solli; et al. (Diagnostics, 2023)
According to the different classifications now in use, thymic tumours are staged by the extent of local invasiveness, and tumour size is not included as a major determinant for the T category. The aim of this double-site retrospective study is to analyse the correlation between tumour dimension and overall survival (OS) in patients who underwent surgical treatment. From January 2000 to December 2020, patients with thymic epithelial tumours who underwent surgical resection were included in this study. Data from a total of 332 patients were analysed. Five- and ten-year overall survival (5–10 YOS) was 89.26% and 87.08%, respectively, while five- and ten-year disease-free survival (DFS) was 88.12% and 84.2%, respectively. Univariate analysis showed a significant correlation between male sex (p-value 0.02), older age (p-value < 0.01), absence of myasthenia gravis (p-value < 0.01), increase in pTNM (pathological Tumor Node Metastasis) (p-value 0.03) and increase in the number of infiltrated organs (p-value 0.02) with an increase in tumour dimension. Tumour dimension alone was not effective in the prediction of DFS and OS, both when considered as a continuous variable and when considered with a cut-off of 3 and 5 cm. However, with multivariate analysis, it was effective in predicting OS in the aforementioned conditions (p-value < 0.01). Moreover, multivariate analysis was also used in the thymoma and Masaoka I subgroups. In our experience, the role of tumour dimension as a descriptor of the T parameter of the TNM (Tumor Node Metastasis) staging system seemed to be useful in improving this system.